Photocatalytic conversion of CO2 to methanol using membrane-integrated Green approach: A review on capture, conversion and purification. Issue 4 (August 2020) - Chakrabortty, Sankha; Nayak, Jayato; Ruj, Biswajit; Pal, Parimal; Kumar, Ramesh; Banerjee, Shirsendu; Sardar, Moumita; Chakraborty, Prasenjit
Graphical abstract: Highlights: Abundantly available CO2 could be converted to renewable fuel methanol. Photo-catalyst integrated adsorbent could be the best choice for high methanol yield from CO2 . Membrane based separation is able to generate very high degree of purification. Solar based membrane distillation system could minimize the overall production cost. Pollutant abatement with simultaneous production of high value bio-energy in single system. Abstract: In the modern world, due to the ever increasing demand of electricity, industrialization and auto-mobilization, the abundance of greenhouse gases has shoot up to a critical level. A critical review has been initiated which provides a comprehensive literatures survey in the last two decades on the novel approaches available on different technologies for the anthropogenic CO2 capturing and conversion to methanol. In addition to that, merits and demerits of existing conventional technologies for downstream separation, purification and concentration enrichment of methanol have been discussed and compared with membrane-based system to find out the best optimal conditions. Extensive literature review reveals that the development of graphene based, TiO2 /CuSO4 coupled photocatalyst for conversion of CO2 to methanol (33–37 mg/g catalyst) and downstream separation and purification using microfiltration membranes (Flux 100-110 L/m 2 h) stand out to be the best possible options for catalyst recycle and product recovery. In the previous studies the conversion was found as low as in the range of 10–20 mg/g catalyst without any development of hydrogen exfoliation graphene based nanocomposite material as well as any integration of spent catalyst recycle or product purification technology based on membrane separation. Such innovation and integration of process design employing cutting-edge schemes not only reduces the concentration of CO2 in biosphere but also produces renewable energy. These efforts towards green manufacturing while confirming the potentials of sustainable business is undeniably essential and should be stimulated.